Control of thrips by injecting imidacloprid into banana pseudostem - Yin, K.S.; Zheng, S.J.; Yang, S.S.; Zeng, L.; Li, X.D.; Guo, Z.X.; Duan, Y.Y.; Yang, P.W.; Xu, S.T.; Yan, H.B.; Zhou, Y.N. (2016)
The banana thrips (Thrips hawaiiensis(Morgan) is a very serious pest in banana plantations. Spraying was main practice against thrips, but the disadvantages were toxicity to beneficial insects and high proportion of no-reaching target. The control effect against thrips was investigated by injecting imidacloprid on banana plant stem. The result showed injecting was safety to banana plant when imidacloprid was diluted 200, 250, 300 times. The control effect with diluting 200 times reached 82.4%， significantly higher than that of diluting 250, 300 times, had no difference with conventional treatment. The occurrence of insecticide injury did not found when imidacloprid was injected diluted 200 times with doses of 20, 40, 60 mL. The control effect against thrips at the doses of 40, 60 mL were 86.3, 89.6% respectively, higher than that at the doses of 20 mL. In conclusion, injecting imidacloprid in banana plants diluting 200 times with the doses of 40 mL was effective way of control thrips. The practice will decrease the insecticide contamination, times of spraying, and provide a practical strategy for sustainable agricultural production in banana plantation.